Impact of Islamic Leadership, Knowledge Management and Labor Motivation on Labor Innovation in Jokotore Bangkalan Batik UKM - Najatun,; Rahmat Hidayat, (Technium Social Sciences Journal, 2023)
The purpose of this study is to investigate the influence of Islamic leaders . Management and Work Motivation for Work Innovation in Batik SMEs from Jokotore Bangkaran Collection . This study is a quantitative study by distributing questionnaires to obtain primary data. Data processing was performed using the Partial Least Squares (PLS) approach for the 54 respondents used in this study to perform the Srobin equation calculations. However, the sample obtained from this study had 61 respondents from the staff of the UKM Batik Jokotore Bangkaran Collection. Statistical test results for this study showed positive and significant results. Work motivation has a great influence on work innovation, but work motivation does not have a great influence on work innovation. This study used a qualitative research approach to analyze the perceptions of 61 Jokotre Batik SMEs. Bangkaran Collection Staff. Improve the introduction of Islamic leadership culture in the field through knowledge management so that employees can increase innovation activities in Jokotre Batik SMEs . Bangalore collection . Put staff to work through knowledge management and contribute to research that Islamic leadership can drive innovation.